How the diversity of human concepts of nature affects conservation of biodiversity - Ducarme, Frédéric (Conservation biology : the journal of the Society for Conservation Biology, 2021)
© 2020 The Authors. Conservation Biology published by Wiley Periodicals LLC on behalf of Society for Conservation Biology.